Near infrared spectroscopy as a potential method to detect bovine respiratory disease - Fox, J.T.; Spire, M.F. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Bovine respiratory disease continues to be the leading cause of illness and death loss from weaning through finishing. There is no objective method to evaluate a live animal’s severity of sickness or their response to treatment. A pilot study was conducted at a commercial feedyard to evaluate the ability of near infrared spectroscopy to differentiate between cattle identified as healthy and those identified as having undifferentiated Bovine Respiratory Disease (BRD). At processing, 215 randomly selected 900 lb heifers were evaluated to determine tissue oxygen saturation (StO2) levels. Mean ranks of the StO2 values were 176.86 ± 5.50. One hundred cattle pulled for clinical signs of bovine respiratory disease were evaluated in the hospital. Animals were classified as: 1st pull, 2nd pull, and 3rd pull on the basis of clinical observations. First-pull animals were those having no previous history of being treated for respiratory disease and having signs of BRD, with rectal temperature at or above 104°F. Second pulls and 3rd pulls were those animals failing to respond to either a first treatment or a second treatment for BRD as evidenced by no improvement in clinical appearance or by rectal temperature remaining above 104°F. Mean StO2 ranks were 110.42 ± 11.29, 120.08 ± 14.48, and 132.83 ± 19.00 for 1st, 2nd, and 3rd pulls, respectively. A significant difference was found between the rank of the StO2 values in cattle at processing and those classified as 1st, 2nd, or 3rd pulls (P<0.05). No difference was found between the three pull classifications. Results provide the basis for further research in the evaluation of BRD with near infrared spectroscopy.
Keywords: Beef; Near infrared spectroscopy; Bovine respiratory disease